The role of axioms in contemporary mathematics in the view of investigations on axiom of choice - Lewandowska, Katarzyna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2011)
We show how philosophy effected the shape of mathematics when the proof of Well-Ordering Principle was formulated by Ernst Zermelo. We also consider the significance of philosophy of mathematics today. We concentrate on Solomon Feferman and Penelope Maddy attitude in the recent debate on the need of new axioms in mathematics.